Предмет: Алгебра,
автор: nasna20
упростите выражение (c^2-b)^2-(c^2-1) (c^2+1)+2bc^2 и найдите его значение при b = -3
Ответы
Автор ответа:
0
Нам понадобятся формулы:
1. (a - b)² = a² - 2ab + b²
2. a² - b² = (a - b)·(a+b)
Получаем:
(c²-b)²-(c²-1) (c²+1)+2bc² = c^4 - 2·c²·b + b²-c^4+1+2·b·c² = b²+1
b = -3, а значит b² = 9
b²+1 = 9+1 = 10
Ответ: 10
1. (a - b)² = a² - 2ab + b²
2. a² - b² = (a - b)·(a+b)
Получаем:
(c²-b)²-(c²-1) (c²+1)+2bc² = c^4 - 2·c²·b + b²-c^4+1+2·b·c² = b²+1
b = -3, а значит b² = 9
b²+1 = 9+1 = 10
Ответ: 10
Похожие вопросы
Предмет: Биология,
автор: OlgaKapitsaOK
Предмет: Русский язык,
автор: danil200891
Предмет: Геометрия,
автор: profia442
Предмет: Математика,
автор: МихаилСоколовский
Предмет: Физика,
автор: Kottek17